2022
DOI: 10.5271/sjweh.4057
|View full text |Cite
|
Sign up to set email alerts
|

Targeting workload to ameliorate risk of heat stress in industrial sugarcane workers

Abstract: Burned cane cutting and seed cutting in industrial sugarcane production are very physically demanding jobs that expose workers to heat strain. Women performing these jobs tend to work at higher workload intensities than male co-workers. Workers' health protections in industrial sugarcane production should consider work intensity as a risk factor when assessing heat stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Other non-mechanized outdoor manual occupations at ISA include repair and management of irrigation tubes and canals, seeding, weeding, and pest control. The physical workload varies between these job groups, but is in many cases high, as previously described (Lucas et al, 2023).…”
Section: Setting and Study Populationmentioning
confidence: 62%
See 2 more Smart Citations
“…Other non-mechanized outdoor manual occupations at ISA include repair and management of irrigation tubes and canals, seeding, weeding, and pest control. The physical workload varies between these job groups, but is in many cases high, as previously described (Lucas et al, 2023).…”
Section: Setting and Study Populationmentioning
confidence: 62%
“…The probable effect magnitude at 14% increase/WBGT °C (95% CI [−5%, 37%]) over the past week is much larger than the 1% risk increase/ambient temperature °C seen in many general populations ( Liu et al, 2021 ). This is most likely explained by the high metabolic workload of the sugarcane workers ( Lucas et al, 2023 ). A high metabolic heat production in a high environmental heat leads to a substantially larger heat stress than low metabolic heat production in the same environmental heat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher productivity in workers aged <45 years as compared to females and older males is likely to be largely a consequence of population-level differences in cardiorespiratory capacity and strength. In a small field-based observational study we have previously shown that women seed cutters work at a higher relative work intensity (based on %HR max ) than their male counterparts ( Lucas et al 2023 ). However, in the current study women workers had a lower sensitivity to heat-related productivity loss (smaller % productivity decline from <28 to >31 WBGT°C ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the RSH intervention improved workers’ productivity during active work periods. Preventing hyperthermia ( Lucas et al 2023 ) and dehydration ( Glaser et al 2020 ) via regulated hourly shaded rest periods with easy access to hydration beverages could have allowed workers to increase their productivity, just as endurance sports athletes perform better when hyperthermia ( Jones et al 2012 ) and dehydration ( Cheuvront, Carter, and Sawka 2003 ) are prevented. Fewer workers developing fever or other symptoms, or biochemical signs of systemic inflammation, were observed with the RSH intervention ( Glaser et al 2020 , 2022 ; Hansson et al 2020 ), likely also contributing to maintaining productivity.…”
Section: Discussionmentioning
confidence: 99%